A Model Islamic Spiritual Guidance in Early Childhood (on Islamic Kindergarten of Salatiga) - Wahidin, Wahidin (Universitas Negeri Semarang, 2015)
Spirituality is an important aspect of human life. Spiritualguidanceiseffort which focuses on helping individuals toreachtheir better life. The purpose of the study is to find out what model of spiritual guidance applied at Islamic Kindergarten (RA) Ma’arif Salatiga. This study used qualitative research as methodology and the object is curriculum at Islamic Kindergarten Ma’arif Salatiga. This study has founded that Islamic Kindergarten Ma’arif Salatiga uses tematic-integral-holistic in the learning procces to apply spiritual guidance. The researcher used descriptive qualitative method for analyzing the data. To apply this concept teachers connect all individual aspect from students based on Islam. The spiritual guidance focuses on helping individuals to be better in living and delivering welfare of their life through the understanding, applying of values, meaning the principles of life in accordance with religion and universal values. Giving spiritual guidance for early childhood plays an important role in the form of future personality. Spirituality is an important aspect of human life. Spiritualguidanceiseffort which focuses on helping individuals toreachtheir better life. The purpose of the study is to find out what model of spiritual guidance applied at Islamic Kindergarten (RA) Ma’arif Salatiga. This study used qualitative research as methodology and the object is curriculum at Islamic Kindergarten Ma’arif Salatiga. This study has founded that Islamic Kindergarten Ma’arif Salatiga uses tematic-integral-holistic in the learning procces to apply spiritual guidance. The researcher used descriptive qualitative method for analyzing the data. To apply this concept teachers connect all individual aspect from students based on Islam. The spiritual guidance focuses on helping individuals to be better in living and delivering welfare of their life through the understanding, applying of values, meaning the principles of life in accordance with religion and universal values​​. Giving spiritual guidance for early childhood plays an important role in the form of future personality. How to citeWahidin, W. (2015). A Model Islamic Spiritual Guidance in Early Childhood (on Islamic Kindergarten of Salatiga). Indonesian Journal Of Early Childhood Education Studies, 4(1), 19-25. doi:10.15294/ijeces.v4i1.9448